Analisis Normatif Terhadap Implementasi Program Pendidikan dan Kesehatan Bagi Narapidana Anak Di LPKA Kelas II Samarinda Dalam Kerangka Peraturan Perundang-Undangan Di Indonesia - Subroto, Mitro; Prasetya, Hendra (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
This study analyzes normatively the implementation of education and health programs for child prisoners at the Samarinda Class II Special Development Institute for Children (LPKA) within the framework of Indonesian legislation. This research uses a normative juridical method with a statutory and conceptual approach, which focuses on the compatibility of program implementation in the field with regulations stipulated in Law No. 35 of 2014 concerning Child Protection and Law No. 11 of 2012 concerning the Child Criminal Justice System, as well as international standards such as the Convention on the Rights of the Child (CRC) and the Beijing Rules. The results show that although LPKA Kelas II Samarinda has attempted to implement education and health programs, there are still various obstacles, including limited facilities, budgets, and professionals that cause a mismatch between regulations and practices. In addition, attention to the mental health of juvenile prisoners is still minimal, which has the potential to hinder their rehabilitation process. In conclusion, improvements are needed in terms of allocating resources, increasing workforce capacity, and strengthening supervision to increase the effectiveness of program implementation and ensure the fulfillment of the rights of child prisoners in accordance with applicable laws and regulations.